Perancangan Sekolah TK Bintang Harapan Kraksaan - Novita Dewi (Intra, 2013)
Kraksaan is one of the emerging city so dibutuhkannyalah touch leader who can reach that dream with both physical and spiritual intelligence. According to Seto, childhood childhood is the best time to shape a person's character. The presence of a container that provides such facilities especially for children (kindergarten Bitang Hope) then the dream can be achieved. Interior of a school has an important role in shaping a person's character. Therefore, it creates a dynamic design concepts (nature of children - children who are likely to want to know and always growing).